Development and Validation of Analytical Methods for Simultaneous Estimation of Lercanidipine Hydrochloride and Enalapril Maleate: Pharmaceutical Science-Pharmaceutical Analysis - J. Patel, Archita; J. Patel, Jamila; G. Patel, Samir (International Journal of Life Science and Pharma Research, 2023)
The fixed dose of lercanidipine hydrochloride(LH) and enalapril maleate (EM) is used to provide more effective control of hypertension. The research work was aimed at the development and validation of simple and sensitive analytical methods for their quantification from tablets. The simultaneous equation, first-order derivative, and multivariate spectrophotometric methods were developed for the simultaneous estimation of LH and EM in tablets. The simultaneous equation method involves a determination of LH and EM at 236 nm and 207 nm, respectively. First order derivative UV spectrophotometry method involves using a zero crossing point of LH at 330 nm and EM at 219 nm. Both methods were validated as per ICH Q2 (R2) guidelines and found to be accurate and precise as they exhibited <2% relative standard deviation. The limit of detection (LOD) and limit of quantitation (LOQ) for LH were found to be 0.26 μg/ml and 0.78 μg/ml respectively whereas LOD and LOQ for EM were found to be 0.41 μg/ml and 1.24 μg/ml respectively for simultaneous equation method. The LOD and LOQ for LH were found to be 0.39 μg/ml and 1.19 μg/ml respectively whereas LOD and LOQ for EM were found to be 0.31 μg/ml and 0.97μg/ml respectively for the first-order derivative method. Three Chemometric methods namely classical least square (CLS), principal component regression (PCR), and partial least square (PLS) were studied for the simultaneous determination of LH and EM in tablets using spectrophotometry. A set of 25 standard mixtures containing both drugs were prepared in the range of 5–25 μg/ml for both drugs. The analytical figure of merit (FOM) was determined for all three chemometric methods. The LOD values for LH were found to be 0.97, 0.93, and 0.94 μg/ml and 0.90,0.88, and 0.89 μg/ml for EM using CLS, PCR, and PLS modeling techniques. The proposed methods were user-friendly, rapid, and sensitive enough for the determination of LH and EM.